IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 11 TAHUN 2000 TENTANG PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI KECAMATAN SEMARANG SELATAN (STUDI TENTANG PENGELOLAAN PEDAGANG KAKI LIMA OLEH PEMERINTAH KOTA SEMARANG) - Yulianto, Galih Dwi; Sundarso, Sundarso (Journal of Public Policy and Management Review, 2017)
The Implementation of the Semarang City Regulation No. 11 Year 2000 on setting And Fostering Street Vendor In District South Semarang is not in accordance with the prescribed rules. Implementation of the Semarang City Regulation No. 11 Year 2000 on setting And Fostering Street Vendor In District South Semarang reap many problems on place setting, licensing and levies so that the background of this study. Research conducted aiming to analyze the implementation of the policy-setting and coaching hawkers in the district of South Semarang, analyzed the factors supporting and implementing policy, and formulate measures necessary to ensure implementation of the policy can be effective. This study uses qualitative research by collecting data through observation, interviews, and documents. The results showed the implementation of regulatory policies and guidance PKL is still not good. This happens because of the lack of the number of officials implementing the policy, the lack of response apparatus against street vendors and there is no SOP. Based on these concerns, there should be efforts to minimize the problems start, increasing the number of officials implementing the policy setting and coaching vendors in terms of the Market Office as the implementing agency shall do the recruitment of employees, increased responsiveness or sensitivity of the apparatus to listen to the aspirations of street vendors and immediately made operational standards procedure (SOP).